Gesture-based Interface for Real-time Control of a Mitsubishi SCARA Robot Manipulator. Issue 25 (2019) - Popov, V.; Ahmed, S.; Shakev, N.; Topalov, A.
Abstract: A new approach to control robot manipulators using body gestures is presented. It implements the Microsoft Kinect sensor ability to track joint positions. The later has been used in the developed software application for gesture recognition, operating in Matlab programming environment, that maps the gestures into robot control commands. The goal is to control the movements of an industrial manipulator that shares its workspace with humans. Such a working environment is characterized with complexity and dynamism. In this way a more-effective interface with the controlled robot can been created. The experimental tests have been carried out with a Mitsubishi SCARA robot manipulator model RH-6CH7020-1D1-S15.